Distribution Analysis of Asiatic Palm Weevil Rhynchophorus vulneratus Panzer (Coleoptera: Dryphthoridae) using GIS Technique and the Interaction with Coconut Beetle Oryctes rhinoceros L. (Coleoptera: Scarabaeidae) - Hanindyo Adi; R.C. Hidayat Soesilohadi; Andhika Puspito Nugroho; Suwarno Hadisusanto; Sudaryatno; Abdulrahman Saad Aldawood; Sukirno Sukirno (Bogor Agricultural University, Indonesia, 2023)
Asiatic palm weevil Rhynchophorus vulneratus Panzer is one of the key pests of coconut in Indonesia. Information regarding the spatial distribution of R. vulneratus is needed to support Integrated Pest Management and can be analyzed using Geographic Information System (GIS). Initial studies on the interaction between R. vulneratus and Oryctes rhinoceros were also studied in this study. This research aimed to analyze the spatial distribution of R. vulneratus using GIS and its interaction with the Coconut beetle Oryctes rhinoceros. The research was conducted in Yogyakarta as a habitat model (0-1,000 masl). R. vulneratus and O. rhinoceros were catched by installing aggregation pheromone traps hanging to coconut plants at 1.7 m above ground. The research was conducted during the rainy and dry seasons. The spatial distribution of R. vulneratus was analyzed by IDW interpolation using QGIS 3.22, whereas its interaction with O. rhinoceros was analyzed by the Pearson correlation test using SPSS 22. The results showed low number of R. vulneratus captured in the Yogyakarta area during the rainy season at 0-1,000 masl. However, the number of R. vulneratus during the dry season has increased, and the distribution rate was dominated by medium to very high levels, especially at an altitude of 0-300 masl. The study also showed that the number of R. vulneratus was not influenced by the number of O. rhinoceros, which suggested that the abundance of O. rhinoceros cannot accurately predict the abundance of R. vulneratus.